Prohibition of Discrimination on Grounds of Nationality in the Freedom of Movement of Persons within the EU in the Light of Case Law of the Court of Justice of the European Union - Bator-Bryła, Monika Patrycja (Review of European and Comparative Law, 2021)
The subject of this article is to analyze the meaning of the prohibition of discrimination on grounds of nationality in the light of the provisions of primary and secondary European Union law and the case law of the Court of Justice of the European Union, which is inherent to the functioning of the internal market and EU citizenship. The prohibition of discrimination on grounds of nationality is undoubtedly one of the main goals of the European Union[1] in the social and economic context, which was reflected in the localization of the matter in question in the primary law of the European Union[2], in secondary law and in the jurisprudence of the Court of Justice of the European Union (CJEU). The Treaty on European Union (TEU)[3] and the Treaty on the Functioning of the European Union (TFEU)[4] indicate equality as one of the EU values (Article 2 TEU), require it to be promoted and combat all discrimination (Articles 8 and 10 TFEU) and prohibit discrimination due to the criteria indicated therein (Articles 18 and 19 TFEU). In secondary law, this principle was expressed primarily in the Regulation of the European Parliament and of the Council No. 492/2011 on the free movement of workers within the Union and in art. 24 of Directive 2004/38/EC 2004 on the right of citizens of the Union and their relatives to move freely[5]. A special role in this area is played by the case law of the Court of Justice of the European Union (CJEU), which stated that all authorities of the Member States are obliged to refuse to apply a provision of national law that is contrary to the prohibition of discrimination on the grounds of citizenship (Article 18 TFEU)[6]. Moreover, national measures may be examined in the light of art. 18 TFEU, but only to the extent that they apply to situations not covered by specific non-discrimination provisions included in the Treaty[7]. The author puts forward the thesis that the analysis of CJEU jurisprudence reveals a visible dissonance between the application of national regulations of the Member States and the provisions of EU law in this matter, which significantly hinders the implementation of the principle of non-discrimination in practice. Discrepancies mainly occur in domestic legal acts due to the improper drafting of national legal provisions and / or their misinterpretation by national judicial or administrative authorities. It should be emphasized that the Member States are obliged to comply with EU law, which is not tantamount only to the obligation of state authorities to respect directly applicable acts, or to implement required regulations into internal law, but also the obligation to interpret and apply internal law in a manner that does not violate the requirement resulting from EU law[8]. Judicial and administrative authorities of the Member States should therefore interpret national law as far as possible, in line with EU law, because the limits of the pro-EU interpretation will be determined by the powers conferred by domestic law[9]. The study uses the legal-comparative method, consisting in a comparative analysis of the legal systems of the Member States and the European Union in the field of non-discrimination on the basis of nationality, rights and restrictions on the freedom of movement of authorized entities. Comparative verification of EU acts with the internal standards of individual EU Member States allows to reveal the degree of advancement of the implementation process of EU law provisions under the free movement of EU citizens and their family members in the discussed area in the legal systems of European Union Member States. The purpose of this analysis is to, inter alia, diagnose areas in which these countries have not implemented or improperly implemented EU regulations, or have misinterpreted them. The second method used is the method of analyzing the jurisprudence of the Court of Justice of the European Union - the rulings of the CJEU constitute a significant part of the study. The case law in question covers the period from the establishment of the Treaties of Rome to the present day. The use of the latter obligated the author to apply the comparative method of judgments based on same or similar legal bases in similar circumstances from different stages of the evolution of the free movement of citizens of the European Union and their family members under the prohibition of discrimination on the basis of nationality. [1] Cf. Olivier De Schutter, Links between migration and discrimination. A legal analysis of the situation in EU Member States (Brussels: European Commission, 2016), 102 and next; See also Brita Sundberg-Weitman, Discrimination on Grounds of Nationality. Free Movement of Workers and Freedom of Establishment under the EEC Treaty (Amsterdam, New York, Oxford: North-Holland Publishing Co., 1977). [2] Erica Szyszczak, “Antidiscrimination Law in the European Union,” Fordham International Law Journal, no. 32 (2008): 635. [3] The Treaty on European Union (consolidated version) OJ of the EU 2012, No. C 326/01. [4] The Treaty on the Functioning of the European Union (consolidated version) OJ of the EU 2012, No. C 326/01. [5] Directive of the European Parliament and of the Council No. 2004/38 on the right of citizens of the Union and their family members to move and reside freely within the territory of the Member States amending Regulation (EEC) No. 1612/68 and repealing Directives 64/221/EEC, 68/360/EEC, 72/194/EEC, 73/148/EEC, 75/34/EEC, 75/35/EEC, 90/364/EEC, 90/365/EEC and 93/96/EEC (O.J.E.C. L 158, 30 April 2004). [6] CJEU Judgement of 7 May 1998, Clean Car Autoservice GmbH p. Landeshauptmann von Wien, Case C-350/96, ECLI:EU:C:1998:205. [7] CJEU Judgement of 18 June 2019, Republic of Austria v Federal Republic of Germany, Case C-591/17, ECLI:EU:C:2019:504, pt 41. [8] Marek Górski, “Wpływ orzecznictwa Europejskiego Trybunału Sprawiedliwości na interpretację i stosowanie przepisów o ochronie środowiska,” in Wspólnotowe prawo ochrony środowiska i jego implementacja w Polsce trzy lata po akcesji, ed. Jerzy Jendrośka and Magdalena Bar (Wrocław: Centrum Prawa Ekologicznego Press, 2008), 31. [9] Monika Niedźwiedź, “Stosowanie prawa wspólnotowego przez organy administracyjne,” Casus, no. 32 (October 2004): 6.